2006
DOI: 10.1179/136485906x105480
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegyptipupal/demographic surveys in southern Mexico: consistency and practicality

Abstract: In interventions aimed at the control of the immature stages of Aedes aegypti (L.), the principal vector of the dengue viruses, attempts are often made to treat or manage all larval habitats in households. When there are resource-constraints, however, a concentration of effort on the types of container that produce the most pupae may be required. Identification of these 'key' container types requires surveys of the immature stages and particularly - since these give the best estimates of the numbers of adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 9 publications
5
25
0
5
Order By: Relevance
“…Thus, difficulties with the inspection of marinas might compromise the success of control actions in coastal areas. Identification of the most productive categories of larval container habitats provides vector control managers with Journal of Insects 7 clues as to the type of breeding sites that should be prioritized in control actions-with consequent reduction in labour and costs-because the most frequent container categories are not necessarily those producing the greatest number of adult mosquitoes [13,[24][25][26]. Our results confirmed that the order of importance of different container categories changed when pupal productivity is taken into account.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, difficulties with the inspection of marinas might compromise the success of control actions in coastal areas. Identification of the most productive categories of larval container habitats provides vector control managers with Journal of Insects 7 clues as to the type of breeding sites that should be prioritized in control actions-with consequent reduction in labour and costs-because the most frequent container categories are not necessarily those producing the greatest number of adult mosquitoes [13,[24][25][26]. Our results confirmed that the order of importance of different container categories changed when pupal productivity is taken into account.…”
Section: Discussionsupporting
confidence: 76%
“…collected, we assumed that all container-breeding species in the study larval surveys were Aedes sp. 25 In October 2007 and October 2008, 6 and 18 months after ITC distribution, 1,101 and 1,013 houses were surveyed in the intervention clusters and 661 and 659 houses were surveyed in the control clusters, respectively. In October 2007, 6 months after ITC distribution, the proportion of households with at least 1 ITC hanging was 70.5% (95% CI = 59.6-81.5%), and the mean number of curtains (all houses included) was 2.17 ITCs/house (95% CI = 1.70-2.64) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…19 However, they are inappropriate for estimating vector densities 20 and of limited use for assessing dengue transmission risk. 21 Work by Focks et al 22 and subsequent multicentre studies [23][24][25] have reconfirmed the usefulness of pupal surveys to identify the types of containers that are epidemiologically important and to estimate adult vector abundance. A further limitation is that dengue vector studies usually focus either on house-holds or on defined public spaces 26,27 and therefore lack the analysis of vector production in defined geographical areas (spatial focus).…”
Section: Introductionmentioning
confidence: 97%